Elastin-based silver-binding proteins with antimicrobial capabilities - Truong, Thi Hong Anh (2013)
Elastin-based biomaterials have gained popularity in tissue engineering and regenerative medicine due to their well-defined chemical and physical properties. In particular, elastin-based materials have tremendous potential as wound dressing materials due to their elasticity and biocompatibility. Yet, elastin-based materials with antimicrobial properties have not been developed to date. In this work, we constructed novel elastin fusion proteins bearing AG3 silver-binding motifs (GPG-AG3) and their thin films. In the presence of NaCl, GPG-AG3 proteins self-assembled to form aggregates with diameters of about 100 nm. Further incubation in silver nitrate yielded silver nanoparticles on the surfaces of the protein particles and thin films. The silver nanoparticles obtained in our work had diameters of 20 – 25 nm from protein aggregates solution and 471 nm ± 178 nm on protein films. The effect of varying NaCl concentrations and pH on the size and morphology of silver particles was examined. The nucleated silver nanoparticles exhibited antibacterial properties when tested against gram-negative E. coli. In both 2xYT agar plates and culture media containing 20 g/mL of synthesized silver, or silver-coated protein films, E. coli growth was completely inhibited. Silver-coated GPG-AG3 films were able to support mammalian cell growth for up to 3 days, but displayed significant cytotoxicity after 7 days. In summary, we have developed GPG-AG3 proteins with the ability to nucleate antibacterial silver particles. In our future work, we will focus on the fabrication of silver nanowires using GPG-AG3 templates. The antibacterial properties and cytotoxicity of silver nanowires will also be examined in vitro.